"We have seen paradoxa today"—What Have We Seen? Brief Thoughts on the Translation of paradoxos in Luke 5.26. Issue 2 (August 2017) - Locker, Markus
This paper assumes that Luke, by using the term paradoxa in Luke 5.26, intends to convey a significance to the words and deeds of Jesus in Luke 5.17-26 that could not have been captured equally well by standard Greek expressions, such as "extraordinary" or "strange." A study of Luke's placement of 5.17-26 in his narrative and a brief survey of the meaning of paradox in antiquity allows for the assumption that paradoxa could mean different things for the various audiences of this scene: "glorious" things for the believer and "inglorious" things for the unbeliever.